Risk of cerebrovascular disease among 13 457 five‐year survivors of childhood cancer: A population‐based cohort study. Issue 3 (7th August 2020) - Reulen, Raoul C.; Guha, Joyeeta; Bright, Chloe J.; Henson, Katherine E.; Feltbower, Richard G.; Hall, Marlous; Kelly, Julie S.; Winter, David L.; Kwok‐Williams, Michelle; Skinner, Roderick; Cutter, David J.; Frobisher, Clare; et al.
Abstract: Survivors of childhood cancer treated with cranial irradiation are at risk of cerebrovascular disease (CVD), but the risks beyond age 50 are unknown. In all, 13457 survivors of childhood cancer included in the population‐based British Childhood Cancer Survivor Study cohort were linked to Hospital Episode Statistics data for England. Risk of CVD related hospitalisation was quantified by standardised hospitalisation ratios (SHRs), absolute excess risks and cumulative incidence. Overall, 315 (2.3%) survivors had been hospitalised at least once for CVD with a 4‐fold risk compared to that expected (95% confidence interval [CI]: 3.7‐4.3). Survivors of a central nervous system (CNS) tumour and leukaemia treated with cranial irradiation were at greatest risk of CVD (SHR = 15.6, 95% CI: 14.0‐17.4; SHR = 5.4; 95% CI: 4.5‐6.5, respectively). Beyond age 60, on average, 3.1% of CNS tumour survivors treated with cranial irradiation were hospitalised annually for CVD (0.4% general population). Cumulative incidence of CVD increased from 16.0% at age 50 to 26.0% at age 65 (general population: 1.4‐4.2%). In conclusion, among CNS tumour survivors treated with cranial irradiation, the risk of CVD continues to increase substantially beyond age 50 up to at least age 65. Such survivors should be: counselled regarding this risk; regularly monitored for hypertension, dyslipidaemia and diabetes; advised on life‐style risk behaviours. Future research should include the recall for counselling and brain MRI to identify subgroups that could benefit from pharmacological or surgical intervention and establishment of a case‐control study to comprehensively determine risk‐factors for CVD. Abstract : What's new? Many sub‐groups of childhood‐cancer survivors have an increased risk of developing adverse health conditions later in life. In our study, the authors found that patients who were treated with cranial irradiation in childhood face a substantially greater risk of cerebrovascular disease after age 50. By age 65, as many as 26% of these patients will have been hospitalised for a cerebrovascular event. These survivors should therefore be counselled regarding lifestyle behaviours to reduce this risk. They should also be regularly monitored for hypertension, dyslipidaemia and diabetes.